(untitled) (REVISTA NODO, 2019)
In addition to its strategic role as a collective transport infrastructure, a bus station is loaded with centrality. It is indeed, since it fosters an efficient symbiosis of a broad articulation of entities, mechanisms and actions. Beyond that, in which technicians and politicians see a mere infrastructural solution, a bus terminal is discovered as a hypersocialized place, framework of a multiple activity in which the bifurcated and contradictory condition of urban life becomes tangible, but also its integrator capacity. All these virtues as a pole of social activity are recognized on the observation of the ordinary life of the Ziguinchor bus station, the most important city of the Casamance, Senegal.